Characterization of a polymorphism in NAD(P)H: quinone oxidoreductase (DT-diaphorase). - Traver, R. D. (Nature Publishing Group, 1997)
NAD(P)H:quinone oxidoreductase (NQO1, EC 1.6.99.2) is an obligate two-electron reductase that can either bioactivate or detoxify quinones and has been proposed to play an important role in chemoprevention. We have previously characterized a homozygous point mutation in the BE human colon carcinoma cell line that leads to a loss of NQO1 activity. Sequence analysis showed that this mutation was at position 609 of the NQO1 cDNA, conferring a proline to serine substitution at position 187 of the NQO1 enzyme. Using polymerase chain reaction (PCR) analysis, we have found that the H596 human non-small-cell lung cancer (NSCLC) cell line has elevated NQO1 mRNA, but no detectable enzyme activity. Sequencing of the coding region of NQO1 from the H596 cells showed the presence of the identical homozygous point mutation present in the BE cell line. Expression and purification of recombinant wild-type and mutant protein from E. coli showed that mutant protein could be detected using immunoblot analysis and had 2% of the enzymatic activity of the wild-type protein. PCR and Northern blot analysis showed moderate to low levels of expression of the correctly sized transcript in the mutant cells. Immunoblot analysis also revealed that recombinant mutant protein was immunoreactive; however, the mutant protein was not detected in the cytosol of either BE or H596 cells, suggesting that the mutant proteins were either not translated or were rapidly degraded. The absence of any detectable, active protein, therefore, appears to be responsible for the lack of NQO1 activity in cells homozygous for the mutation. A polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) analysis for the mutation at position 609 conducted on 90 human lung tissue samples (45 matched sets of tumour and uninvolved tissue) revealed a 7% incidence of individuals homozygous for the mutation, and 42% heterozygous for the mutation. These data suggest that the mutation at position 609 represents a polymorphism in an important xenobiotic metabolizing enzyme, which has implications for cancer therapy, chemoprevention and chemoprotection. IMAGES: